Treatment of gingival recession with collagen membrane and DFDBA: a histometric study in dogs - Elizabeth Pimentel Rosetti; Rosemary Adriana Chiérici Marcantonio; Joni Augusto Cirelli; Elizangela Partata Zuza; Elcio Marcantonio Jr (Sociedade Brasileira de Pesquisa Odontológica, 2009)
In a previous study, we evaluated the findings related to the use of resorbable collagen membranes in humans along with DFDBA (demineralized freeze-dried bone allograft). The aim of this subsequent study was to histometrically evaluate in dogs, the healing response of gingival recessions treated with collagen membrane + DFDBA (Guided Tissue Regeneration, GTR) compared to a coronally positioned flap (CPF). Two types of treatment were randomly carried out in a split-mouth study. Group 1 was considered as test (GTR: collagen membrane + DFDBA), whereas Group 2 stood for the control (only CPF). The dogs were given chemical bacterial plaque control with 0.2% chlorhexidine digluconate during a 90-day repair period. Afterwards, the animals were killed to obtain biopsies and histometric evaluation of the process of cementum and bone formation, epithelial migration and gingival level. A statistically significant difference was found between groups with a larger extension of neoformed cementum (GTR = 32.72%; CPF = 18.82%; p = 0.0004), new bone (GTR = 23.20%; CPF = 09.90%; p = 0.0401) and with a smaller area of residual gingival recession in the test group (GTR = 50.69%; CPF = 59.73%; p = 0.0055) compared to the control group. The only item assessed that showed no statistical difference was epithelial proliferation on the root surface, with means of 15.14% for the GTR group and 20.34% for the CPF group (p = 0.0890). Within the limits of this study we concluded that the treatment of gingival recession defects with GTR, associating collagen membrane with DFDBA, showed better outcomes in terms of a larger extension of neoformed cementum and bone, as well as in terms of a smaller proportion of residual recessions.